[Meal in Agricultural Building] (1977)
An older man with arms crossed standing, looking directly into the camera, behind a table where people of mixed ages are eating a meal. Appears to be inside an agricultural building with a rough floor and raised sides with chair desks. An image of a bull and trophies are in a case at the back wall. Construction of the building appears to be metal siding with tensioning rods, like barn walls.